The analysis of flour blends as affected by the behaviour of two different quality flours of triticale under different fertilizer treatments - Ács, Erika; Bóna, Lajos; Langó, Bernadett; Pepó, Péter; Petróczi, István (Acta Agraria Debreceniensis, 2016)
Triticale is likely used in many countries in human consumption, due to its advantageous agronomical and nutritional properties mostly in blends. The baking quality of blends depends not just on the proportions of the used flours but also on their individual quality what can be influenced by fertilizer treatments. 22 flour blends were prepared with commercial wheat flour and triticale wholemeal flour in proportions from 0% to 100%. The triticale was treated with different amount of fertilizers (N30P30K30, N60P0K0). Changes of wet gluten contents and extensograph parameters of the blends were determined. The quality of blends significantly depends on the fertilizer treatment of triticale beside the proportions of the flours. When the N60P0K0 treated triticale was used in blends, wet gluten and extensibility values were significantly higher, but in case of resistant to extensions (Rmax) the N30P30K30 treated samples gave higher values. The measured values of wet gluten and extensibility were above the expected values (synergism), while in the case of resistance to extension the expected values were higher than the measured values (antagonism).